(untitled) (Western European Journal of Medicine and Medical Science, 2026)
The hypothalamic–pituitary system is one of the most important neuroendocrine regulatory mechanisms in the human body. This article discusses the anatomical structure, physiological functions, and clinical significance of the hypothalamus and pituitary gland. The hypothalamus serves as the central coordinating center between the nervous and endocrine systems, while the pituitary gland functions as the major endocrine regulator controlling peripheral glands. The article explains the hormonal interactions between the hypothalamus and pituitary gland, including releasing and inhibiting hormones, trophic hormones, and feedback regulation mechanisms. Special attention is given to the hypothalamic–pituitary axes involved in metabolism, growth, reproduction, stress adaptation, and water balance. Furthermore, common pathological conditions associated with dysfunction of this system, such as pituitary adenomas, Cushing Syndrome, acromegaly, and Diabetes Insipidus, are briefly described. Understanding the anatomical and functional importance of the hypothalamic–pituitary system is essential in the fields of Endocrinology, physiology, and clinical medicine.